Review of Stability Enhancement for Formamidinium‐Based Perovskites. Issue 9 (15th August 2019) - Fan, Yingping; Meng, Hongguang; Wang, Li; Pang, Shuping
Abstract : Organic–inorganic hybrid perovskites (OIHPs) are one of the hottest fields on account of their immense potential for photovoltaics. As one of the most promising OIHPs, formamidinium (FA)‐based perovskites have been developed very fast in the past few years. The power conversion efficiency (PCE) has reached certified 24.2%, which is comparable with that of monocrystalline silicon solar cells. However, the easy formation of nonperovskite δ‐phase formamidinium lead triiodide (FAPbI3 ) at a low temperature needs to be solved when fabricating a high‐quality light absorber layer. Several strategies have been used to avoid the formation of δ‐phase FAPbI3 and improve phase stability in recent years such as tolerance factor adjustment, dimensional engineering, addictive processing, interfacial modification, defects passivation, and in situ growth. These approaches can enhance the phase stability to some extent; however, their contribution to long‐term stability and especially their real mechanism is still unknown. Herein, the relationships among the tolerance factors, the structure of FAPbI3, and the phase transition phenomenon are summarized. In addition, various methodologies and potential mechanisms for stabilizing α‐phase FAPbI3 at room temperature (RT) are discussed. In conclusion, a series of challenges in the popular processings of perovskite solar cells and their corresponding solutions that help achieve commercialization faster are summarized. Abstract : Perovskite solar cells are very promising for their high efficiency and solution‐process feasibility. Herein, some fabrication methods for gaining a high‐quality perovskite layer with long‐term stability are reviewed. These approaches significantly enhance the stability of perovskites, which makes it applicable for commercialization. However, these methods have some issues and it still leaves much room for further optimization.